INTERFERENCE PROCESSES IN TEACHING ENGLISH AND GERMAN GRAMMARS TO FUTURE PHILOLOGISTS - Лілія Морська (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2014)
The analysis of factors influencing the interlanguage interference in the course of the study of contact foreign languages has been carried out, which laid the basis for further analysis of a set of classifications of interference types. The negative influence of Ukrainian and German grammars on English grammar has been analyzed. The interference classifications have been characterized. Morphological and syntactic grammar interferences in the process of teaching and learning English grammar after German of future philologists have been substantiated, their types have been characterized. The division of grammar interference according to psycholinguistic aspects has been defined, possible ways for the defined interference prevention in simultaneous study of the mentioned foreign languages have been suggested